Example: Downsampling by 2

For $ N=2$ , downsampling by 2 can be expressed as $ y(n) = x(2n)$ , so that (since $ W_2\isdef e^{-j2\pi/2}=-1$ )

\begin{eqnarray*}
Y(z) &=& \frac{1}{2}\left[X\left(W^0_2 z^{1/2}\right) + X\left(W^1_2 z^{1/2}\right)\right] \\ [5pt]
&=& \frac{1}{2}\left[X\left(e^{-j2\pi 0/2} z^{1/2}\right) + X\left(e^{-j2\pi 1/2}z^{1/2}\right)\right] \\ [5pt]
&=& \frac{1}{2}\left[X\left(z^{1/2}\right) + X\left(-z^{1/2}\right)\right] \\ [5pt]
&=& \frac{1}{2}\left[\hbox{\sc Stretch}_2(X) + \hbox{\sc Stretch}_2\left(\hbox{\sc Shift}_\pi(X)\right)\right].
\end{eqnarray*}


Next Section:
Example: Upsampling by 2
Previous Section:
Tightening the IFFTs